Exploration of Literary Narrative Through the Exile Experience of Mas Marco Kartodikromo - Dinda Nasya Atin; Tegar Catur Kurniawan; Yesi Kumalasari (International Forum of Researchers and Lecturers, 2024)
This research explores literary narratives through Mas Marco Kartodikromo's experience of exile. By analyzing the literary works he produced during his exile, this research aims to understand how the experience of exile influenced the literary narratives produced by Mas Marco Kartodikromo. Through this approach, this research provides insight into the relationship between personal experiences and literary works.